BIOMARKERS FOR ASYNCHRONOUS AGING IN CHRONIC HIV INFECTION. (11th November 2018) - Montano, M; Tran, T; Guardigni, V; Hale, T; Vegreville, M; Roitmann, E; Storer, T
Abstract: Human immunodeficiency virus (HIV)-infected individuals are at increased risk of age-associated functional impairment, even with effective antiretroviral therapy (ART). Whether accelerated aging occurs in chronic HIV infection and the biological mechanisms that underlay aging with chronic HIV infection remains unclear. We undertook a prospective observational study of 170 middle-aged, HIV-infected ambulatory men and women with CD4+ T-cell counts of at least 350 per ml and undetectable plasma viremia while on effective antiretroviral therapy, and uninfected control participants. We measured biomarkers for inflammation and immune activation, fatigue, the Veterans Aging Cohort Study (VACS) mortality index, and conducted physical function assessment and accelerometer tracking. A subset of participants also received a skeletal muscle biopsy and computerized tomography scan. Compared to the uninfected, HIV+ participants displayed increased immune activation (P<0·001), inflammation (P=0·001) and fatigue (P=0·010), and in a regression model adjusting for age and sex displayed deficits in stair climb power (P<0.001), gait speed (P=0.036) and predicted metabolic equivalents (P=0.019). Skeletal muscle displayed reduced nuclear PGC-1alpha positive myonuclei (P=0·006) and increased internalized myonuclei (P<0·001) that correlated with immune activation (P=0·003) and leukocyte infiltration (P<0·001). Activity tracking with accelerometers revealed deficits in gait speed and activity patterns in HIV infection. Asymptomatic HIV-infected middle-aged adults display atypical skeletal muscle profiles, subclinical deficits in physical function and persistent inflammation and immune activation, that collectively are distinct from canonical mechanisms of biological aging. Identifying biomarker profiles for risk of future functional decline in the asynchronously aging HIV-infected population will be key to developing and monitoring preventative interventions.